The Role of Primary School Students in Working on the Texts in Textbooks and the Development of Children's Speaking Competencies (For Primary School Students in Karakalpak Schools) - Nilufar, Kamalova (Pindus Journal of Culture, Literature, and ELT, 2022)
The article provides information about the work of primary school students in the textbooks of Karakalpak language schools on the texts cited in the textbooks and the role of these texts in the development of children's speech, increasing vocabulary. 'analyzed through examples given in the study programs.